Transmisi Kemiskinan Antargenerasi di Indonesia Tahun 1993–2014, Studi Data IFLS - Irwan, Memy; Moeis, Jossy P. (Jurnal Ekonomi dan Pembangunan Indonesia, 2019)
The initial hypothesis states that children from poor household have a tendency to return to poverty as an adult. This is because children from poor household are more difficult to utilize available resources than children from non-poor household. By using McNemar test, the data proved that there was a transmission of poverty in Indonesia during 1993–2014. In other words, poverty alleviation program in Indonesia had not been successfully carried out. Multinomial logit was used to analyzed factors that influence the transmission of poverty. There are various factors that affect the intergenerational transmission of poverty in Indonesia, namely the level of education and health, the ownership of movable assets and the existence of school facilities.